Miniaturized Vortex Ultrasound Transducers with Different Topological Charges - Jing Wang; Huaiyu Wu; Mengyue Chen; S. M. Abu Naser Shovon; Henry Ware; Chengzhi Shi; Xiaoning Jiang (Advanced Devices & Instrumentation)
Vortex ultrasound has attracted increasing research interest in biomedical engineering such as complex particle manipulation, communication speed improvement, ultrasound imaging edge enhancement, targeted drug delivery, noninvasive therapies, fast blood clot lysis, and tissue ablation. This work presents a way to generate vortex ultrasound waves by integrating a spiral phase structure with a miniaturized transducer. The assembly overcomes the drawbacks of existing transducer arrays such as complicated fabrication, costly multichannel amplifiers, and pricey feedback circuits by providing precise control over topological charges and continuous phase modulation. To assess the design, numerical simulations, analytical calculations, and experimental validation were performed. Transducer prototypes with a central frequency of 5 MHz showed transmitting sensitivity of 12.31 kPa/V peak to peak (Vpp) and 6.15 kPa/Vpp for the peak-to-peak pressure and peak negative pressure, respectively. An acoustic intensity of 0.22 W/cm2 was measured at 13-Vpp input to the device, which agrees with simulation results. In summary, this work offers a promising path for vortex ultrasound generation with minimal complexity, affordable manufacturing, and compatibility with different transducers compared to traditional arrays.